Regulasi Emosi dan Depresi pada Remaja: Rapid Systematic Literature Review - Fadillah Fira Firmanilah (SOCIETIES: Journal of Social Sciences and Humanities, 2026)
Abstract. This rapid systematic literature review synthesizes evidence on the relationship between emotion regulation and depression among adolescents by prioritizing publications from the last five years. Guided by PRISMA 2020 principles, a structured search was conducted across PubMed, PubMed Central, SpringerLink, ScienceDirect, Google Scholar, and Indonesian psychology journals for publications from 2021 to 2025. Eligible studies involved adolescent or youth samples, examined emotion regulation strategies, emotion dysregulation, emotional awareness, family-level regulation, or emotion regulation flexibility, and reported depressive symptoms or related internalizing outcomes. Sixteen recent core studies were synthesized thematically. The review indicates that maladaptive strategies, especially rumination, catastrophizing, self-blame, suppression, emotional nonacceptance, and limited regulatory strategies, are consistently associated with higher depressive symptoms. Adaptive strategies, such as cognitive reappraisal, acceptance, problem solving, emotional clarity, and regulatory flexibility, tend to be protective, although their effects depend on developmental stage, social context, family climate, and the fit between strategy and situational demands. The review concludes that adolescent depression should be addressed through emotional literacy, flexible regulation, family support, and school-based prevention. Keywords: adolescent; depression; emotion regulation; mental health; rapid systematic review